Clinical Outcomes and Vaccine Effectiveness for SARS-CoV-2 Infection in People Attending Advanced CKD Clinics: A Retrospective Provincial Cohort Study. Issue 4 (16th April 2023) - Roushani, Jian; Thomas, Doneal; Oliver, Matthew J.; Ip, Jane; Yeung, Angie; Tang, Yiwen; Brimble, Kenneth Scott; Levin, Adeera; Hladunewich, Michelle A.; Cooper, Rebecca; Blake, Peter G.
Visual Abstract: Abstract : Background: People with advanced CKD are at high risk of mortality and morbidity from coronavirus disease 2019 (COVID-19). We measured rates of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and severe outcomes in a large population attending advanced CKD clinics during the first 21 months of the pandemic. We examined risk factors for infection and case fatality, and we assessed vaccine effectiveness in this population. Methods: In this retrospective cohort study, we analyzed data on demographics, diagnosed SARS-CoV-2 infection rates, outcomes, and associated risk factors, including vaccine effectiveness, for people attending a province-wide network of advanced CKD clinics during the first four waves of the pandemic in Ontario, Canada. Results: In a population of 20, 235 patients with advanced CKD, 607 were diagnosed with SARS-CoV-2 infection over 21 months. The case fatality rate at 30 days was 19% overall but declined from 29% in the first wave to 14% in the fourth. Hospitalization and intensive care unit (ICU) admission rates were 41% and 12%, respectively, and 4% started long-term dialysis within 90 days. Significant risk factors for diagnosed infection on multivariable analysis included lower eGFR, higher Charlson Comorbidity Index, attending advanced CKD clinics for more than 2 years, non-White ethnicity, lower income, living in the Greater Toronto Area, and long-term care home residency. Being doubly vaccinated was associated with lower 30-day case fatality rate (odds ratio [OR], 0.11; 95% confidence interval [CI], 0.03 to 0.52). Older age (OR, 1.06 per year; 95% CI, 1.04 to 1.08) and higher Charlson Comorbidity Index (OR, 1.11 per unit; 95% CI, 1.01 to 1.23) were associated with higher 30-day case fatality rate. Conclusions: People attending advanced CKD clinics and diagnosed with SARS-CoV-2 infection in the first 21 months of the pandemic had high case fatality and hospitalization rates. Fatality rates were significantly lower in those who were doubly vaccinated. Podcast: This article contains a podcast at https://dts.podtrac.com/redirect.mp3/www.asn-online.org/media/podcast/CJASN/2023_04_10_CJN10560922.mp3